The dependence of Non-Timber Forest Produts (NTFP’s) to Temiar Community in Pos Brooke, Gua Musang, Kelantan - Shahrin, Nurul Hazni (2019)
Forest offers many materials and services either directly or indirectly to the societies. For communities who are living near or inside the forest, they are dependent on forest for many aspects of their livelihood. The knowledge on extent of these uses to local community especially indigenous people is still lacking and rarely understood. This thesis examined the socioeconomic aspects of the indigenous people specifically the Temiar tribe at Pos Brooke, Gua Musang, Kelantan. Objectives of this study is to determine their income dependency on forest. Data were gathered by using in-depth interview method and questionnaires were distributed randomly to the Temiar people within their community and presented using the detailed statistical analysis. Results indicated that the forest resources had generated the economic benefits through their daily economic activities which contributed to their incomes. This study also revealed that a total of 63% respondents were involved in forest resources product collected activities, 7% involved in agriculture, 12% involved in business and 18% involved in farming. Medicinal plants, rattan, bamboo, honey, gaharu and handicraft were among the forest products that were beneficial for their income. However, the overall results of this study showed that the economic activity by the Temiar community depends on forest resources to fulfil their daily needs in terms of food, traditional medicine and shelter.